Optimising Islamic Education for Young Children Through Contextual Learning - Yuyus Susilawati (Islamic Journal of Education, 2025)
Early childhood education is an effort aimed at children from birth to six years of age, carried out through the provision of educational stimuli to assist physical and spiritual growth and development so that children are prepared to enter further education. For this reason, the instilling of Islamic values needs to be carried out from an early age so that it becomes a strong foundation in shaping the character of students. The research method used was a qualitative approach with a literature study method. The results showed that the contextual approach emphasized the involvement of students in understanding the material through direct experience, so that their understanding of Islamic values as a strong foundation for character building became more optimal. The contextual learning model can be applied to all subjects, with the aim of enabling students to be more actively involved in learning and constructing their knowledge independently, thereby optimising their understanding of Islamic values as a strong foundation for character building in early childhood